Ethical Issues in Prison Psychiatry - Konrad, Norbert.; Vl̲lm, Birgit.; Weisstub, David N. (International Library of Ethics, Law, and the New Medicine, 2013)
Recent surveys demonstrate a high and possibly increasing prevalence of mental disorders in prisoners. They have an increased risk of suffering from a mental disorder that transcends countries and diagnoses. Ethical dilemmas in prison psychiatry arise from resource allocation and include issues of patient choice and autonomy in an inherently coercive environment. Ethical conflicts may arise from the dual role of forensic psychiatrists giving raise to tensions between patient care/protection of the public.This book describes models and ethical issues of psychiatric healthcare in prison in several countries. Relevant issues are: the professional medical role of a psychiatrist and/or psychotherapist working in prison, the involvement of psychiatrists in disciplinary or coercive measures; consent to treatment, the use of coercion in forcing a prisoner to undergo treatment, hunger strike, confidentiality. The book ends with consensus guidelines concerning good practice in Prison Psychiatry.